2021
DOI: 10.1136/bmjopen-2020-044149
|View full text |Cite
|
Sign up to set email alerts
|

Modelling COVID-19 transmission in Africa: countrywise projections of total and severe infections under different lockdown scenarios

Abstract: ObjectivesAs of 13 January 2021, there have been 3 113 963 confirmed cases of SARS-CoV-2 and 74 619 deaths across the African continent. Despite relatively lower numbers of cases initially, many African countries are now experiencing an exponential increase in case numbers. Estimates of the progression of disease and potential impact of different interventions are needed to inform policymaking decisions. Herein, we model the possible trajectory of SARS-CoV-2 in 52 African countries under different intervention… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 42 publications
4
34
0
1
Order By: Relevance
“…Our observations are consistent with recent studies from Nigeria, Ethiopia, Malawi, Zimbabwe and elsewhere in SSA [14][15][16][17][18][19]. While these findings have been attributed largely to the direct effects of the COVID-19 lockdowns, Thakur et al and others [15][16][17] have suggested that other factors unrelated to the COVID-19 pandemic may be contributory.…”
Section: Discussionsupporting
confidence: 92%
“…Our observations are consistent with recent studies from Nigeria, Ethiopia, Malawi, Zimbabwe and elsewhere in SSA [14][15][16][17][18][19]. While these findings have been attributed largely to the direct effects of the COVID-19 lockdowns, Thakur et al and others [15][16][17] have suggested that other factors unrelated to the COVID-19 pandemic may be contributory.…”
Section: Discussionsupporting
confidence: 92%
“…The basic reproduction number is 2.76 which is consistent with results from other computations, e.g. [23].…”
Section: Resultssupporting
confidence: 90%
“…The surface is bounded by curves defined by constant values of mitigation and relaxation percentages. We have already seen that hard lockdown was defined as mitigation of 44% and moderate lockdown as mitigation of 25% [23]; it is therefore reasonable to start with mitigation percentages in the range (25, 50). Relaxation techniques applied after mitigation are designed to increase the transmission rate, preferably to 80% - 90% of the pre-mitigation transmission.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations